Clinical Activity and Tolerability of a 14-Day Infusional Ifosfamide Schedule in Soft-Tissue Sarcoma. (4th December 2013) - Martin-Liberal, Juan; Alam, Salma; Constantinidou, Anastasia; Fisher, Cyril; Khabra, Komel; Messiou, Christina; Olmos, David; Mitchell, Scott; Al-Muderis, Omar; Miah, Aisha; Linch, Mark; Jones, Robin L.; et al.
Abstract : Background . Soft-tissue sarcomas (STS) are a heterogeneous group of diseases with lack of effective treatments in most cases. Previous data suggest that continuous infusional ifosfamide regimens might improve cytotoxicity and tolerability compared to standard schedules. Methods . We retrospectively report the outcome of 35 patients affected by STS treated with a 14-day infusional ifosfamide regimen (1000 mg/m 2 /day) in our institution. Predictive factors for toxicity were also explored. Results . Median age was 53 years. There were 16 males and 19 females. Classification by histology was dedifferentiated liposarcoma (DDLPS): 22 (62.8%), synovial sarcoma: 7 (20%), myxoid/round-cell liposarcoma: 3 (8.5%), and others: 3 (8.5%). Overall, 7 patients (20%) achieved partial response (PR) and 10 patients (29%) achieved stable disease (SD). DDLPS showed special sensitivity: 5 patients (22.7%) had PR, 7 patients (31.8%) had SD, and disease control rate was 54.5%. Median progression-free survival and overall survival were 4.2 and 11.2 months, respectively. The most common toxicities were fatigue, nausea, and vomiting (all grades: 85.7%, 83%, and 54.3%, resp.). Neither hypoalbuminaemia nor gender was found to predict toxicity, although encephalopathy predominantly affected females. Conclusion . Ifosfamide administered as a 14-day continuous infusion is a safe regimen in STS with notable activity in DDLPS.